Influence of glass composition on photoluminescence from Ge2+ or Ag nano‐cluster in germanate glasses for white light‐emitting diodes. Issue 3 (31st August 2018) - Zhao, Jingyuan; Yang, Zhengwen; Yu, Chengye; Qiu, Jianbei; Song, Zhiguo
Abstract: Germanium glass has attracted much interest because of its potential application as the optical waveguides and communication devices. In this work, germanium glass was prepared, exhibiting the blue luminescence at the 410 nm from the Ge 2+ . The influence of SiO2 addition in the germanate glass on the 410 nm luminescence of the Ge 2+ was observed. The SiO2 addition promoted the formation of Ge 2+, which is because the Si 4+ ions can deprive the O 2− ions from the Ge 4+ ion caused by the lower optical basicity of Si 4+ ions than Ge 4+ ion. The germanium glasses containing the Ag nano‐clusters were prepared using ion‐exchange method. The influence of SiO2 concentration on the size of Ag nano‐clusters was observed, which stabilize the size distribution and lead to the miniaturization of Ag nano‐clusters. The Ag nano‐clusters size dependence of their photoluminescence was observed in germanate glasses, and the tunable photoluminescence of Ag nano‐clusters was obtained by controlling the size of Ag nano‐clusters. It is noticed that the Ag nano‐clusters formed in the germanate glass showed the white light emission characteristic excited at the blue chip, exhibiting the practical application as the blue converted white light‐emitting diodes.